Impact of System of Rice Intensification (SRI) on Production of Paddy among Practicing Farmers - Rahangdale, Deepti; Agrawal, S.K.; Pyasi, V.K.; Dubey, M.K. (Indian Journal of Extension Education, 2011)
In India, rice is the most important staple food crop for about two thirds of the population. It is a means of livelihood for millions of rural households and it plays a vital role in our national food security. The recent break through in rice cultivation known as system of Rice. Intensification (SRI) method is the one which can be considered as per disembodied technology SRI is a new system of rice cultivation for increasing productivity with a comprehensive package of practices involving less seed, water chemical fertilizers and pesticides. Balaghat block was selected purposively because it has the highest coverage of SRI method of paddy cultivation. Out of Total 149 villages only 6 villages where the SRI production practices are adopted by rice growers has been selected. A comprehensive list of SRI practicing farmers of each selected village has been prepared and 20 farmers from each selected village has been selected on the basis of simple random sampling without replacement method. Thus, the sample consist of 120 farmers. The study concluded that the level of education, land holding, social participation, mass media exposure extension participation, knowledge level of SRI technology, economic motivation and adoption level were found to be significant with production level of paddy among SRI practicing farmers, whereas age, farm power, annual income, closeness with extension agent and aspiration level had showed non significant association with production level of paddy among SRI practicing farmers.